ANTIDIABETIC EFFECT OF COMBINED Muntingia calabura L. LEAF EXTRACT AND METFORMIN ON RATS - Nugroho, Adhy; Primanagara, Risnandya; Basyir, Pahmi Budiman Sahputra (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2019)
Background: Diabetes mellitus is a disease that causes blood glucose levels to increase. There are several therapies that can be done to reduce blood glucose levels in diabetes such as metformin, biguanides medicine and kersen (Muntingia calabura L.) leaves as an alternative. Treatment with combination of both is expected to further reduce blood glucose levels. This study aims to measure the effectiveness of the combination of metformin and Muntingia calabura L. leaf extract on blood glucose levels. Methods: This was an experimental research with pretest-posttest control group. The samples were 24 Sprague-Dawley rats divided into 4 groups, first group (K1) negative control was given only aquadest, second group (K2) positive control (+) was given 45 mg/kgBW metformin, third group (K3) was treated with 300 mg/kgBW Muntingia calabura leaf extract, and the fourth group (K4) was given the combination of 300 mg/kgBW Muntingia calabura leaf extract and 45 mg/kgBW metformin. Blood glucose levels were measured and analyzed using paired t-test and one-way ANOVA. Results: The combination of 300 mg/kgBW of Muntingia calabura extract and 45 mg/kgBB of metformin reduces 131.77 ± 3.57 mg/dl of blood glucose levels (p<0.05). This result is better than only metformin (92.68 ± 3.10 mg/dl) or only Muntingia calabura leaf extract (91.70 ± 4.40 mg/dl). There is a possibility that the synergistic effect of Muntingia calabura leaf extract and metformin caused the increased effectivity in reducing blood sugar level.Conclusion: The combination of Muntingia calabura and metformin is more effective in reducing blood glucose levels compared to a single dose of metformin or Muntingia calabura L. extract alone.